Optimalisasi Pengawasan pada Penerimaan Pendaftaran Merek dalam Rangka Perlindungan Merek - FEBRI NOOR HEDIATI (Universitas Negeri Surabaya, 2020)
The writing of this law examines the supervision of the Directorate General of Intellectual Property of the Ministry of Law and Human Rights in the process of receiving trademark registration which is still weak. So that until now there are still identical or counterfeit brands that have passed trademark registration in Indonesia. This paper uses a normative juridical research method that is descriptive-analytical. The result of this research is that there are still gaps that can be exploited by individuals in the process of trademark registration, especially in the process of announcing the official brand news. This paper concludes the need for tighter supervision by utilizing information technology, therefore creating a smartphone application is useful for the trademark registration process and as a medium of communication. The application can also provide notifications when brands validity period ends.